Colistin Heteroresistance Is Largely Undetected among Carbapenem-Resistant Enterobacterales in the United States - Victor I. Band (American Society for Microbiology, 2021)

(untitled)
Heteroresistance is an underappreciated phenomenon that may be the cause of some unexplained antibiotic treatment failures. Misclassification of heteroresistant isolates as susceptible may lead to inappropriate therapy.